Chromosome variability in the Chagas disease vector Rhodnius pallescens (Hemiptera, Reduviidae, Rhodniini) (2008)
ABSTRACT: Rhodnius pallescens is the main vector of Trypanosoma cruzi in Panama and one of the most relevant secondary vectors in Colombia. Despite the importance of this species, there is limited knowledge about the genetic variability along its geographical distribution. In order to evaluate the degree of karyotype variability we analyzed the meiotic behavior and banding pattern of the chromosomes of 112 males of R. pallescens coming from different regions of Colombia and Panama. Using the C-banding technique we identified two chromosomal patterns or cytotypes characterized by differences in the amount, size and distribution of constitutive heterochromatic regions in the chromosome complement (2n = 20 autosomes plus XY in males). The individuals can be easily classified in each cytotype by the analysis of the chromosomes during first meiotic prophase. The frequencies of the cytotypes are variable according to the geographic origin of the populations. This chromosomal divergence together with morphological data supports the existence of three genetically different populations of R. pallescens and provides new information to understand the distribution dynamics of this species.